Burden of Ulcerative Colitis on Functioning and Well-being: A Systematic Literature Review of the SF-36® Health Survey. (23rd February 2018) - Yarlas, Aaron; Rubin, David T; Panés, Julian; Lindsay, James O; Vermeire, Séverine; Bayliss, Martha; Cappelleri, Joseph C; Maher, Stephen; Bushmakin, Andrew G; Chen, Lea Ann; DiBonaventura, Marco
Abstract: Background and Aims: This review is the first to evaluate the burden of ulcerative colitis [UC] on patients' quality of life by synthesizing data from studies comparing scores from the SF-36® Health Survey, a generic measure assessing eight quality-of-life domains, between UC patients and matched reference samples. Methods: A systematic review of the published literature identified articles reporting SF-36 domains or physical and mental component summary scores [PCS, MCS] from UC and reference samples. Burden of disease for each SF-36 domain was then summarized across studies by comparing weighted mean differences in scores between patient and reference samples with minimally important difference thresholds. Results: Thirty articles met pre-specified inclusion criteria. SF-36 scores were extracted from five samples of patients with active disease, 11 samples with a mixture of disease activity, five samples of patients in clinical remission, and 13 samples of patients following proctocolectomy with ileostomy or ileal pouch-anal anastomosis, along with respective reference samples. Clinically meaningful burden was observed in samples with active or mixed disease activity [deficits: PCS = 5.6, MCS = 5.5] on all SF-36 domains except Physical Functioning. No burden was observed in samples in remission or post-surgical patients [deficits: PCS = 0.8, MCS = 0.4] except for the General Health perception domain. Conclusions: Patients with active UC experience a clinically meaningful burden of disease across most aspects of quality of life. Patients with inactive UC exhibit negligible disease burden and are comparable to the general population on most quality-of-life outcomes. Thus, treatments which effectively induce and maintain remission may restore physical and mental health status.